FINANCIAL MANAGEMENT IN INSTITUTIONS OPERATING IN GOVERNMENT SECTORS - Qusay Ahmed Dawoud (Scholars Digest Publishing, 2024)
The research aims primarily to enable those working in financial management to have full knowledge of the nature of their work and their difficulties in applying general standards, instructions and applicable laws. We have tried as much as possible to draw the general frameworks for financial management operating in all government sector institutions by highlighting aspects of its work, importance, and objectives. For which it was created. To achieve this, the deductive approach was adopted in the theoretical aspect of the research, and it reached a set of conclusions, the most important of which is that the role of financial management is focused on monitoring, controlling, protecting, and preparing reports on the financial resources of institutions. Institutions also have accountants or financial teams responsible for managing their funds, including all financial transactions, investments and other sources of financing. The researcher recommended a set of recommendations, the most important of which are the necessity of continuous monitoring of public money, the method of its management, and the development of successful plans to implement the public budgets of all state institutions. It is also necessary to establish an organizational structure for financial management consistent with applicable laws and instructions.
Keywords: financial management, planning, performance evaluation.